Largo Caballero : inter-departmental correspondence - Bolton, W. J.
013-0032-001 W.J. BOLTON. INTERNATIONAL. SIR WALTER CITRINE K.B.E 12TH NOVEMBER, 1941. LARGO CABALLERO. A telegram has been received from Negrin, Paddington, London, saying that Largo Caballero was in danger of being delivered by the Vichy Government to Franco, and asking you to intervene. On 15th November 1940 we were told that Largo Caballero had been handed over, and was going to be tried by a Court Martial. We wrote a letter to Lord Halifax who replied that he would consult with the Ambassador, at the same time pointing out the difficulties about doing anything effective. Shall I write again to the Foreign Office? 292/946/13/32